Attention AND mentalizing? Reframing a debate on social orienting of attention - Capozzi, Francesca; Ristic, Jelena (Visual cognition, 2020)
People spontaneously attend where others are looking. Recently, it has been debated whether such orienting behaviour is supported by domain-general attentional processes, that involve reading the cues' directional properties, or by processes that involve attributing mental states to agents. In this Opinion, we summarize key evidence for each position and argue that instead of favouring one or the other view, the available data point to an integrated framework in which the attribution of mental states and the operation of domain-general attentional processes both contribute to social orienting. In addition to providing a novel perspective, this view opens several fruitful future research avenues aimed at understanding how the two processes act together to influence cognitions and behaviour.